Victim-Offender Mediation: Observations from Scandinavia - Mari-Louise Pabsdorff; Lise-Lotte Rytterbro; Saija Sambou; Erika Uotila (Oñati Socio-Legal Series)
Mediation in the aftermath of conflicts and crimes is getting more common in the European countries. This study analyses the discourse between the parties and mediator(s) during mediation in three Scandinavian countries. Mediation talk is much concentrated on the crime situation, on the actions of the parties and other persons present at the time of the crime. Central to the discourse is “accounts”; an analytical term developed by Scott and Lyman in the 1960’s. Explanations of the crime are primarily found on an individual level, leaving societal issues out: A normative and evaluative inquiry of crimes and why crimes occur play a minimal (if any) role in VOM in Scandinavia.